Native ureter substitution for entire necrotized ureter after cadaveric kidney transplantation: A case report. - Siriboonrid, Satit; Kanrchanatarayont, Sarayuth; Jiraanankul, Vittaya; Viriyabundithkul, Veerayuth; Binsri, Nattapong (Insight Urology, 2019)
Native ureter substitution for entire necrotized ureter after cadaveric kidney transplantation: A case report. Satit Siriboonrid MD, Sarayuth Kanrchanatarayont MD, Vittaya Jiraanankul, Veerayuth Viriyabundithkul MD and Nattapong Binsri MD Division of Urology, Department of Surgery, Phramongkutklao Hospital, Bangkok, Thailand Introduction Kidney transplantation is the best of kidney replacement therapies for end stage renal disease patients due to best results and less mobilities when compare to hemodialysis that bring it more popular in Thailand. Even though less complications, but some complication can make morbidity and in the worst case is graft loss. Ureteral necrosis is one of those complications. Case description 50-year-old received allograft from cadaveric donor with prolonged cold ischemic time. Extensive dissection when procurement make naked renal pedicle and entire ureter. After procedure of transplantation, urine still leakage to drainage site. Conservative measurement was unsuccessful. Native ureter was recruited for long-defect correction. Result Native pyeloureterostomy was done with retained larger bore ureteric stent. Urinary leakage was stoped in the first day. All of catheters were removed in same duration of non-complicated case of kidney transplantation. Allograft was good function, and hemodialysis was withdrawn from this case. Conclusion Native ureter substitution is one of choice of entire necrotized ureter that provide good results and accepted complication. Key words: Necrotized ureter, kidney transplantation, native ureter